MENGEMBANGKAN KEWIRAUSAHAAN SOSIAL BERBASIS LINGKUNGAN UNTUK PEMBERDAYAAN KELUARGA MELALUI PENDIDIKAN PAUD - Desi Wulandari; Lili fauziah (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Early Childhood Education (PAUD) has a crucial role in shaping children's character and basic knowledge, including in terms of environmental awareness. On the other hand, many families in Indonesia are facing economic challenges that require intervention to improve their well-being. This research aims to develop environment-based social entrepreneurship as a tool for family empowerment through early childhood education. Environment-based social entrepreneurship not only aims to create profitable businesses, but also to support the sustainability of nature, thus having a positive impact on both the family economy and environmental conservation. Through literature research, it was found that the integration of social entrepreneurship with early childhood education can provide dual benefits: increasing environmental awareness in children and empowering parents with eco-friendly entrepreneurial skills that can increase family income. Collaboration between educational institutions, the government, and the community is also considered very important to ensure the successful implementation of this program.